Pre-start conditions in freestyle wrestlers - Iliev, I. (International Journal of Wrestling Science, 2022)
PURPOSE: This study revealed the characteristics of pre-start anxiety in freestyle wrestling athletes. The task of the study was to find out the intensity in the structure of athletes' pre-competition anxiety.